Lords of the sea a history of the Barbary Corsairs - Jamieson, A. G. (Alan G.) (Reaktion Books Ltd, 2012)
Lords of the Sea is an engrossing tale of piracy, maritime conquest, slavery and exploration that details the history of the Barbary corsairs. Jamieson artfully explains how these Muslim corsairs from the Ottoman Turkish empire captured Christian ships for centuries.